Feed efficiency in swine - Patience, John F.; SpringerLink (Online service) (Wageningen : Wageningen Academic Publishers : Imprint: Wageningen Academic Publishers, 2012)
'Feed efficiency in swine' has been prepared as a comprehensive treatise on the current state of our understanding of this topic which is so important to the pork industry. Each chapter is written by international authorities who understand both the science and application of their topic area. The book provides detailed insight into the many factors affecting feed efficiency, ranging from diet processing to herd health, from nutrition to physiology and from day-to-day barn management to the adoption of advanced technologies. The authors explain such practical aspects as the challenge of interpreting feed efficiency information obtained on farm or the role of liquid feeding. The authors also delve into more scientific topics such as amino acid or energy metabolism or animal physiology. This book is written for people who have a technical interest in pork production, including nutritionists, geneticists, farm management specialists, veterinarians, other academics and, of course, pork producers.
Preface -- 1. Herd management factors that influence whole herd feed efficiency; A.M. Gaines et al -- 2. Feeding and barn management strategies that maximize feed efficiency; M.D. Tokach et al -- 3. Liquid feeding corn-based diets to growing pigs: practical considerations and use of co-products; C.F.M. de Lange, C.H. Zhu -- 4. Amino acid nutrition and feed efficiency; C.F.M. de Lange et al -- 5. The influence of dietary energy on feed efficiency in grow-finish swine; J.F. Patience -- 6. Feed processing to maximize feed efficiency; C.R. Stark -- 7. The genetic and biological basis of residual feed intake as a measure of feed efficiency; J.M. Young, J.C.M. Dekkers -- 8. Pig breeding for improved feed efficiency; P.W. Knap, L. Wang -- 9. Effect of climatic environment on feed efficiency in swine; D. Renaudeau et al -- 10. Fueling the immune response: what$1 (Bs the cost?; R.W. Johnson -- 11. Influence of health on feed efficiency; S.S. Dritz -- 12. Physiology of feed efficiency in the pig: emphasis on the gastrointestinal tract and specific dietary examples; J.R. Pluske -- 13. Emerging technologies with the potential to improve feed efficiency in swine; F.R. Dunshea.s
Keywords: Life sciences; Life Sciences; Life Sciences, general